Implementation of a computer-guided consultation in the assessment of suspected obstructive sleep apnoea syndrome. Issue 3 (27th July 2020) - Chakrabarti, Biswajit; Lewis-Burke, Nadia; Pearson, Mike; Craig, Sonya; Davies, Lisa; Sheridan, Kim; England, Philip; McKnight, Eddie; Angus, Robert
Background: We describe implementation of a clinical decision support system, a computer-guided consultation (CGC), in the assessment of subjects referred with suspected obstructive sleep apnoea syndrome (OSAS). Methods: Two cohorts of patients were assessed. The first 100 cases had data collected with the CGC by a specialist sleep physician (stage1). A further 100 cases were assessed by a nonspecialist using the CGC (stage 2). For each case, the diagnosis suggested by the CGC was compared with the final diagnosis made by a second specialist sleep physician blinded to the CGC diagnosis. Results: Stage 1: of 100 people evaluated, a final diagnosis of OSAS was made by both the sleep specialist and CGC in 88% of cases. In 7 of the remaining 12 cases, both agreed there was "No evidence of OSAS"; in 5 cases the CGC did not reach a final diagnosis instead prompting specialist referral. Stage 2: 100 people were evaluated; 95% were evaluable. Both CGC and the sleep specialist made a diagnosis of OSAS in 83 cases (87%), in 5 cases both agreed there was no OSAS, whereas in 7 cases the CGC prompted a specialist review due to unexplained symptoms. The CGC was concordant with the final diagnosis in 95% and 93% of cases in the two cohorts, respectively and where there was doubt, prompted for clinical review. No OSAS cases were overlooked by the CGC. Conclusion: An intelligent CGC program creates opportunities in sleep medicine management pathways to safely yet effectively utilise nonspecialists working under specialist supervision. A clinical decision support system may be used safely to assess subjects with suspected obstructive sleep apnoea syndrome when used by specialists and nonspecialists alike https://bit.ly/2AFPD0r